Produktivitet och lönsamhet vid skogsbränsleuttag längs skogsbilvägar - Edlund, Marita (SLU/Dept. of Forest Resource Management, 2009)
With an increased demand for biomass based energy and with development of better technique harvest biomass, new possibilities open up. With the possibility to combine traditional cleaning of road's right of way with biomass harvesting, the work of suppressing tree vegetation could become profitable or at least decrease the road maintenance cost. However, knowledge about productivity and profitability in mechanical biomass harvesting in roads' right of ways are still limited. Therefore a productivity study of a Rottne H8 harvester with an accumulating Naarva-harvester head was conducted. The study was performed in, respectively, three study units with small trees (2 cm mean diameter in breast height (dbh)), medium sized trees (3 cm dbh) and large trees (4 cm dbh) along a forest road. The average productivity for the machine was 2,7 tones of dry matter (DM) biomass per productive hour (E0-hour). The subsequent forwarding and chipping of the material were also studied. The total cost for all processing and transport to industry were calculated and compared to the income for the chipped biomass. The mean net income was 15 108 SEK/ha. Roads having medium and large sized trees in their right of ways were profitable to harvest (net income 20 599 – 34 457 SEK/ha) with the studied system. The harvesting of small trees resulted in a cost (9 733 SEK/ha) which were larger than the costs for expanded traditional cleaning (5 600 – 7 000 SEK/ha). The costs and incomes related to this kind of harvest should be compared to the future costs that can be avoided as a result of the improvement durability of roads. Directly profitable or not, the maintenance of roads' right of way should therefore be seen as an investment in future road quality.